2014
DOI: 10.1128/ec.00062-14
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase N1 (EtAPN1), an M1 Metalloprotease of the Apicomplexan Parasite Eimeria tenella, Participates in Parasite Development

Abstract: Aminopeptidases N are metalloproteases of the M1 family that have been reported in numerous apicomplexan parasites, including Plasmodium, Toxoplasma, Cryptosporidium, and Eimeria. While investigating the potency of aminopeptidases as therapeutic targets against coccidiosis, one of the most important avian diseases caused by the genus Eimeria, we identified and characterized Eimeria tenella aminopeptidase N1 (EtAPN1). Its inhibition by bestatin and amastatin, as well as its reactivation by divalent ions, is typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Fluorogenic substrates, derived from unnatural α-amino acids that comprise bulky hydrophobic P1 side-chain residues bearing a fragment of a basic character, were ranked among the most favored ligands. A similar hydrophobic and base-oriented P1 specificity profile was observed for mammalian (human and porcine) [5] and protozoan ( Plasmodium falciparum [6] and Eimeria tenella [7]) alanine aminopeptidases, the abundantly spread metallohydrolases of multiple functions and medical implications [8-10]. The privileged features of the amino acid substrates can be readily translated into the structure of potential inhibitors.…”
Section: Introductionmentioning
confidence: 71%
“…Fluorogenic substrates, derived from unnatural α-amino acids that comprise bulky hydrophobic P1 side-chain residues bearing a fragment of a basic character, were ranked among the most favored ligands. A similar hydrophobic and base-oriented P1 specificity profile was observed for mammalian (human and porcine) [5] and protozoan ( Plasmodium falciparum [6] and Eimeria tenella [7]) alanine aminopeptidases, the abundantly spread metallohydrolases of multiple functions and medical implications [8-10]. The privileged features of the amino acid substrates can be readily translated into the structure of potential inhibitors.…”
Section: Introductionmentioning
confidence: 71%
“…The CRISPR-Cas9-mediated genome editing approach should soon keep its promises and allow the generation of knockout virulence-attenuated strains that may be valuable for vaccination. (Bussiere et al, 2018;Gras et al, 2014) were maintained by serial passages in chicken. Freshly excysted sporozoites were purified as described (Bussiere et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…E. tenella Wisconsin strain (Wis) expressing yellow fluorescent protein (YFP) or E. tenella INRA strain expressing mCherry fluorescent protein (Bussiere et al, ; Gras et al, ) were maintained by serial passages in chicken. Freshly excysted sporozoites were purified as described (Bussiere et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the sporoplasm release was prevented by 1,10-phenanthroline (metalloprotease) and it suggested that metalloprotease is related the sporoplasm release in K. septempunctata [26]. Metalloproteases of parasite have been related to pathogenesis and are involved in processes such as immunity evasion, development, and metabolism [8,17]. In addition, the activity of metalloproteases are affected by pH of environment [13].…”
Section: Discussionmentioning
confidence: 99%